Comparison of the rate of certain trace metals accumulation in indoor plants for smoking and non-smoking areas - Ghoma, Wasem Esmael Omer; Sevik, Hakan; Isinkaralar, Kaan (Springer Science and Business Media LLC, 2023)
Tobacco smoke causes to release severe toxic metals into the environment. It is recognized as the most significant issue in indoor air quality. Pollution and toxic substances in smoke quickly spread and penetrate the indoor environment. Environmental tobacco smoke is responsible for lowering indoor air quality. There is much evidence that poor air quality occurs with inadequate ventilation conditions in indoor environments. The plants have been observed to absorb the smoke in the environment into their own body like a sponge. The plant species in this study can be used easily in almost every office, home, or other indoor areas. Using indoor plants is very beneficial in biomonitoring and absorbing these trace metals. Some indoor plants have shown successful performance as biomonitors for health-damaging pollutants. The study aims to determine the concentration of three trace metals (Cu, Co, and Ni) using five indoor ornamentals frequently used in smoking areas, namely D. amoena, D. marginata, F. elastica, S. wallisii, and Y. massengena. The Ni uptake and its accumulation in S. wallisii, and Y. massengena increased in correlation with smoke areas. However, the rate of accumulation of Co and Cu was found to be independent due to consideration of the environmental emissions. Consequently, our results suggest that F. elastica is more resistant to smoking, whereas S. wallisii would be a better choice as a biomonitoring plant of tobacco smoke.
Keywords: Air Pollution, Indoor; Air Pollution; Tobacco Smoke Pollution; Rubber; Biological Monitoring; Environmental Monitoring; 13. Climate action; 11. Sustainability